Microbial Consortiums of Hydrogenotrophic Methanogenic Mixed Cultures in Lab-Scale Ex-Situ Biogas Upgrading Systems under Different Conditions of Temperature, pH and CO - Jun Xu; Fan Bu; Wenzhe Zhu; Gang Luo; Li Xie (Microorganisms, 2020)
In this study, hydrogenotrophic methanogenic mixed cultures taken from 13 lab-scale ex-situ biogas upgrading systems under different temperature (20–70 °C), pH (6.0–8.5), and CO (0–10%, v/v) variables were systematically investigated. High-throughput 16S rRNA gene sequencing was used to identify the microbial consortia, and statistical analyses were conducted to reveal the microbial diversity, the core functional microbes, and their correlative relationships with tested variables. Overall, bacterial community was more complex than the archaea community in all mixed cultures. Hydrogenotrophic methanogens Methanothermobacter, Methanobacterium, and Methanomassiliicoccus, and putative syntrophic acetate-oxidizing bacterium Coprothermobacter and Caldanaerobacter were found to predominate, but the core functional microbes varied under different conditions. Multivariable sensitivity analysis indicated that temperature (p < 0.01) was the crucial variable to determine the microbial consortium structures in hydrogenotrophic methanogenic mixed cultures. pH (0.01 < p < 0.05) significantly interfered with the relative abundance of dominant archaea. Although CO did not affect community (p > 0.1), some potential CO-utilizing syntrophic metabolisms might be enhanced. Understanding of microbial consortia in the hydrogenotrophic methanogenic mixed cultures related to environmental variables was a great advance to reveal the microbial ecology in microbial biogas upgrading process.